METACOGNITIVE SKILLS AND MOTIVATION DIFFERENCES BETWEEN MALE AND FEMALE Xth GRADE STUDENT OF PUBLIC SENIOR HIGH SCHOOL IN MALANG THROUGH READING QUESTIONING AND ANSWERING (RQA) COMBINED WITH THINK PAIR SHARE (TPS) LEARNING STRATEGY - Hindun Syarifah; Sri Endah Indriwati; Aloysius Duran Corebima (JPBI (Jurnal Pendidikan Biologi Indonesia), 2016)
Student diversity issue in school is one of the subjects in educational research. The quite apparent problem of student diversity in the school is gender differences. Male and female are different in some ways. Several studies have revealed the influence of gender differences on a wide range of students' abilities. Mahanal (2011) revealed that there was an effect of gender differences on metacognition skills and critical thinking abilities of high school students in Malang city. This research is aimed to determine the metacognition skills and motivation differences of male and female student on the biology subject through the implementation of Reading Questioning and Answering (RQA) combined with Think Pair Share (TPS) learning strategies. This research used quasy-experiment of pre test- post test nonequivalent group design. The research populations were all of